Does the Systemic Immune Inflammation Index and Plasma Atherogenic Index Predict Poor Prognosis in Patients Undergoing Mitral Balloon Valvuloplasty? - Nergiz Aydın; Sefa Tatar; Ahmet Taha Şahin; Yakup Alsancak (Gazi Medical Journal)
Objective: In this study, we aimed to investigate the impact of the systemic immune-inflammation index (SII) and plasma atherogenic index (PAI) on adverse outcomes in patients undergoing percutaneous mitral balloon valvuloplasty (PMBV). A 5-year follow-up was conducted in patients with mitral stenosis who underwent PMBV, assessing all-cause mortality, major adverse cardiovascular events (MACE), surgical need for the mitral valve, and requirement for repeat PMBV. Methods: This single-center retrospective study included 103 patients who underwent PMBV due to rheumatic mitral valve disease between January 2014 and January 2019. Demographic characteristics and pre- and postprocedural echocardiographic data of the patients were analyzed. The 5-year follow-up included assessments of all-cause mortality, MACE, surgical requirement for the mitral valve, and rates of repeat PMBV. Laboratory parameters at admission and at the third-month follow-up were recorded through a review of patient records. Results: A total of 103 patients (75 females) with a mean age of 41.81±14.83 years were enrolled in the study. At admission, the SII was calculated as 8.49±6.27, PAI as 0.45±0.25, and the mitral valve area (MVA) as 1.16±0.19 cm2. Post-procedurally, MVA increased to 1.72±0.23 (p=0.001). At the third-month follow-up, SII was 7.77±7.16, and PAI was 0.47±0.25. While a statistically significant decrease was observed in SII post-procedure (p<0.001), no significant change was noted in PAI (p=0.843). When examining 5-year MACE rates in the deceased group, the SII at admission was 765.5±577.3, and at the third month, it was 794.2±907.6 (p>0.05). Regarding 5-year MACE rates in the deceased group, the PAI value at admission was 0.4±0.41, and at the third month, it was 0.4±0.42 (p>0.05). Conclusion: In patients undergoing PMBV, SII is a significant parameter indicating a reduction in inflammation. However, both SII and PAI are insufficient for predicting the 5-year MACE frequency after PMBV. Additional parameters are required to indicate poor prognosis.